2013
DOI: 10.1186/1471-2458-13-700
|View full text |Cite
|
Sign up to set email alerts
|

The association between self-reported lack of sleep, low vitality and impaired glucose tolerance: a Swedish cross-sectional study

Abstract: BackgroundThe increased incidence of impaired glucose tolerance (IGT), are serious public health issues, and several studies link sleeping disorders with increased risk of developing type 2 diabetes, impaired glucose tolerance and insulin resistance (IR). This study explore how self-reported lack of sleep and low vitality, are associated with IGT in a representative Swedish population.MethodsA cross-sectional survey conducted in two municipalities in South-western Sweden. Participants aged 30–75 were randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Severely short sleep, defined by some as ≤5 h per night, as well as insomnia has been previously linked to a significantly increased risk of T2DM [ 18 ] and increased insulin resistance [ 39 ] through validated sleep measures. Lack of self-reported sleep [ 40 ] as well as sleep debt [ 41 ] has also been linked to the condition. These sleep outcomes (insomnia, lack of sleep and sleep debt) may be due to poor-quality sleep, which has resulted in researchers investigating this in relation to diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Severely short sleep, defined by some as ≤5 h per night, as well as insomnia has been previously linked to a significantly increased risk of T2DM [ 18 ] and increased insulin resistance [ 39 ] through validated sleep measures. Lack of self-reported sleep [ 40 ] as well as sleep debt [ 41 ] has also been linked to the condition. These sleep outcomes (insomnia, lack of sleep and sleep debt) may be due to poor-quality sleep, which has resulted in researchers investigating this in relation to diabetes.…”
Section: Introductionmentioning
confidence: 99%
“… 30 Consistently, a study from Sweden confirmed that short sleep duration in men was associated with an increased incidence of diabetes 31 and impaired glucose tolerance. 32 Recent studies reported that both short and long sleep durations were associated with diabetes in men but not in women. 33–35 …”
Section: Discussionmentioning
confidence: 99%
“…)”], exercise habits (yes/no answers to “Do you exercise more than 30 minutes, more than twice in a week and have continued this exercise habit for more than one year?”), and self-reported sufficiency of sleep (yes/no answers to “Getting enough sleep?”). We included the self-reported sufficiency of sleep as a CVD risk factor because of a previous study’s suggestion that self-reported lack of sleep was associated with impaired glucose tolerance ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…"), and selfreported sufficiency of sleep (yes/no answers to "Getting enough sleep?"). We included the self-reported sufficiency of sleep as a CVD risk factor because of a previous study's suggestion that self-reported lack of sleep was associated with impaired glucose tolerance (23).…”
Section: Cvd Risk Factorsmentioning
confidence: 99%